The Effect Of Blood Transfusion On The Risk Of Hepatitis B Infection In Hemodialysis Patients : Meta Analysis - Astuti, Yuli; Dewi, Yulia Lanti Retno; Murti, Bhisma (Poltekkes Kemenkes Semarang, 2025)
Background Hepatitis B is caused by infection with the Hepatitis B virus, this disease affects 240-280 million people in the world. Hepatitis B virus causes chronic disease that develops in liver damage, cirrhosis and liver cancer, more than 600,000 people die every year. Giving repeated blood transfusions increases a person's risk of developing hepatitis infection. Hemodialysis patients who receive blood transfusion therapy are more at risk of developing hepatitis infection. Objective of this study was to study and estimate the influence of blood transfusion history on the risk of hepatitis B infection in hemodialysis patients based on the results of previous similar studies by meta-analysis. Method is a meta-analysis conducted by searching for articles from the databased Google Scholar, PubMed, Springer Link, and Research Gate. The keywords used were